Padrões de concorrência no mercado brasileiro de torrefação e moagem de café e 1997 - 2005 - Steinberg, Marcel (2006)
This dissertation aims at analysing the patterns of competition from the period of 1997-2005 in the Brazilian roasted and grounded market. For the development of this research, a questionary elaborated by the researchers Maria Sylvia M. Saes and Elizabeth M. M. Q. Farina, that was utilized with the firms associated to the Associação Brasileira da Indústria de Café (ABIC) in 1997, will be used. The same questionary will be replicated in the year 2006 in order to capture changes within the patterns of competition along those 9 years. The methodology applied in this study is the case study, with unit of analysis being the Brazilian roasted and grounded industry. The research will be descripitive, since it will describe the pattern of competition in the Brazilian roasted and grounded market. However, the study is also exploratory due to the fact that there isn't any research that analyzes the specific object of study. The results obtained suggest that, taking into consideration the relevant variables of structure, conduct and performance of the industry of roasted and grounded coffee, the pattern of competition remained the same throughout the period 1997-2005.